Molecular Characterization and Functional Study of Insulin-Like Androgenic Gland Hormone Gene in the Red Swamp Crayfish, Procambarus clarkii - Shi, Linlin (Genes (Basel), 2019)
The androgenic gland (AG) is a male-specific endocrine organ that controls the primary and secondary sexual characteristics in male crustaceans. More evidence indicates that the insulin-like androgenic gland hormone gene (IAG) is the key male sexual differentiation factor, particularly the application of RNA interference (RNAi) technology on IAG. In this study, the full-length cDNA of IAG (termed PcIAG) was isolated from the red swamp crayfish, Procambarus clarkii. Tissue distribution analysis showed that in addition to its expression in the AG of male P. clarkii, PcIAG was widely expressed in female tissues and other male tissues. The PcIAG protein was detected in the reproductive and nervous systems of adult male P. clarkii. Additionally, RNAi results showed that the PcIAG expression could be silenced efficiently, and the male sperm maturation and release possibly present a transient adverse interference at lower doses (0.1 μg/g and 1 μg/g) of PcIAG–dsRNA (PcIAG double-stranded RNA). Dramatically, the expression level of PcIAG increased sharply shortly after the injection of higher doses (5 μg/g and 10 μg/g) of PcIAG–dsRNA, which might accelerate the maturation and release of sperm. Moreover, the expression of PcSxl (P. clarkii Sex-lethal) was detected by Quantitative Real-Time PCR (qPCR) after the injection of PcIAG–dsRNA to explore whether the PcIAG gene regulates the PcSxl gene, and we found that the PcIAG did not directly regulate PcSxl in P. clarkii. The study could help accelerate the progress of PcIAG functional research and provide a useful reference for the single-sex selective breeding of P. clarkii.